PENANAMAN NILAI-NILAI MULTIKULTURAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA MA’ARIF SUKOREJO - Alfani Apriliani Nirmawati; Tarisa Febrianti; Latifatul Naima (Journal Multicultural of Islamic Education, 2023)
This research aims to explore the potential and effectiveness of instilling multicultural values ​​in Islamic Religious Education (PAI) learning at SMA Ma'arif Sukorejo. The research method involves in-depth analysis of the PAI curriculum, direct observation of the learning process, as well as in-depth interviews with experienced PAI teachers. The use of qualitative methods in this research was chosen. The data sources used consisted of primary and secondary data. Primary data was obtained through interviews with respondents such as the Principal, Islamic Religious Education teachers, and students in classes X-XI-XII at SMA Ma'arif Sukorejo. Meanwhile, secondary data is obtained from documents and publications that have been processed by other parties. Data collection techniques used include observation, interviews and documentation. Qualitative data analysis is carried out interactively and continuously until the data is considered to have reached the level of saturation. The data analysis process involves data collection, data reduction (selection, grouping, and elimination of irrelevant data), data presentation, and drawing conclusions. The research results show that there is significant room for integrating multicultural values ​​in PAI learning. With the right approach, PAI learning can be a vehicle for forming inclusive, tolerant and respectful attitudes between students from various cultural and religious backgrounds.